Assessing the National Sanitation Policy in Rwanda - Kazora, Amos Shyaka; Mourad, Khaldoon A (Review of Environment and Earth Sciences, 2018)
Populated cities in Rwanda rely on decentralized wastewater management systems due to the absence of central sewerage systems and the limited finances for sanitation infrastructures. This paper studied the influence of the national sanitation policy and the best available technologies in addressing and reinforcing decentralized wastewater treatment practices in Kigali city such as on-site and off-site sanitation systems. Different sanitation and wastewater management related policies were reviewed with emphasis on densely populated cities. The paper highlighted the need for a sustainable sanitation policy focusing on the safe disposal of the wastewaters and the proper connection to protect the ecosystem and to improve the status of the sanitation services in Rwanda. It was also noted that policies cannot be implemented without a real intervention of the local authorities in monitoring, advising and putting practical guidelines for individuals and communities before and after constructing their treatment systems.